Does Accounting Digitalization Bring Business Efficiency And Effectiveness? - Marjulin, Marjulin; Hilmi, Hilmi; Mustaqim, Teuku; Syafrizal, Said Herry; Faisal, Faisal (International Journal of Social Service and Research, 2025)
The purpose of this study is to discover the basic truth through deductive analysis and then prove it with empirical facts regarding digital accounting in achieving business efficiency and effectiveness. The object of this study is MSMEs in Aceh. The research design uses quantitative methods collected from 50 MSMEs and qualitative data collected through questionnaires. This study will apply knowledge and science by verifying whether the basic concepts and their application of digital accounting in achieving MSME business efficiency and effectiveness. Verification is carried out by empirically proving it with MSME actors. The results of the study prove the concepts that have been studied and are expected to show that digital accounting can have an impact on achieving business efficiency and effectiveness. Thus, through the proposed conceptual framework model, it can provide solutions to overcome problems in increasing the resulting efficiency and effectiveness. The use of digital accounting as an input will result in increased business efficiency and effectiveness as its output.